Notch-Signaling Deregulation Induces Myeloid-Derived Suppressor Cells in T-Cell Acute Lymphoblastic Leukemia - Grazioli, Paola; Orlando, Andrea; Giordano, Nike; Noce, Claudia; Peruzzi, Giovanna; Abdollahzadeh, Behnaz; Screpanti, Isabella; Campese, Antonio Francesco (Frontiers in Immunology, 2022)
Notch receptors deeply influence T-cell development and differentiation, and their dysregulation represents a frequent causative event in “T-cell acute lymphoblastic leukemia” (T-ALL). “Myeloid-derived suppressor cells” (MDSCs) inhibit host immune responses in the tumor environment, favoring cancer progression, as reported in solid and hematologic tumors, with the notable exception of T-ALL. Here, we prove that Notch-signaling deregulation in immature T cells promotes CD11b+Gr-1+ MDSCs in the Notch3-transgenic murine model of T-ALL. Indeed, aberrant T cells from these mice can induce MDSCs in vitro, as well as in immunodeficient hosts. Conversely, anti-Gr1-mediated depletion of MDSCs in T-ALL-bearing mice reduces proliferation and expansion of malignant T cells. Interestingly, the coculture with Notch-dependent T-ALL cell lines, sustains the induction of human CD14+HLA-DRlow/neg MDSCs from healthy-donor PBMCs that are impaired upon exposure to gamma-secretase inhibitors. Notch-independent T-ALL cells do not induce MDSCs, suggesting that Notch-signaling activation is crucial for this process. Finally, in both murine and human models, IL-6 mediates MDSC induction, which is significantly reversed by treatment with neutralizing antibodies. Overall, our results unveil a novel role of Notch-deregulated T cells in modifying the T-ALL environment and represent a strong premise for the clinical assessment of MDSCs in T-ALL patients.